Restorative Justice in Criminal Law: Assessing Its Role in Reducing Recidivism Rates - Lucia Sandoval; Carlos Velasquez (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study evaluates the effectiveness of restorative justice approaches in reducing recidivism among offenders. By examining case studies and statistical data from restorative programs across various countries, the article assesses the impact of restorative justice on offender rehabilitation, victim satisfaction, and community healing. Findings suggest that while restorative justice can significantly reduce re-offense rates for certain crimes, its success depends on structured implementation and societal support for alternative justice methods. This paper highlights the potential of restorative justice to address the root causes of crime, fostering positive outcomes for offenders, victims, and communities.